PENYULUHAN TENTANG PELAYANAN PROGRAM RUJUK BALIK (PRB) BPJS KESEHATAN - Abdul Zaky; Marido Bisra; Atika Wulandari (Awal Bros Journal of Community Development, 2021)
Healthcare and Social Security Agency is one of the health programs facilitated by the government. In order to improve the quality and ease of access to health services for all participants, Healthcare and Social Security Agency has offered a service program called the referral program (RP). The amount of public misunderstanding of the program is a challenge for Healthcare and Social Security Agency service officers and the government. Therefore it is necessary to make efforts to provide an understanding to the public about the program. The community service activities have been carried out in RW 1 Kulim Village, Kulim District, Pekanbaru City, in order to assist the government's task to provide understanding to the community. The method of community service activities carried out is by distributing brochures, giving lectures by resource persons, discussions and questions and answers. As for the results of this community activity, the community has understood what a referral program (RP) is and how to get a referral program. The evaluation of this community service activity was also carried out through a discussion forum with the village and sub-district leaders of Kulim. In the evaluation activity, village and sub-district leaders said that this activity provided benefits for the community.